Practical aspects of grass forage seed production and quality with particular reference to planting row spacing and nitrogen fertilization in tropical regions: A review - GBENOU, Basile; ADJOLOHOUN, SÉBASTIEN; Houndjo, Daniel; Ahoton, Léonard E; SAIDOU, ALIOU; HOUINATO, MARCEL ROMUALD BENJAMIN; SEIBOU TOLEBA, Soumanou; Sinsin, Brice A. (My University, 2018)
The poor seed yield from some pasture grasses may result from a number of causes, such as the choice of site production, low soil fertility, inappropriate sowing rate, inadequate crop management practices particularly plant density, fertilizer input, poor seed recovery, etc. Compared with sowings of general plant use, seed crops warrant more care and expense during the establishment phase. Seedbeds should be prepared more thoroughly and the seed sown more precisely using adequate seeding rates. The effect of row spacing on the one hand and nitrogen level application on the other hand, have variable effect on grass seed production and there are a conflicting report in some cases depending on species, management practices and environmental conditions, and therefore a case-by-case study for each species and environment is important. In general, seed growers had better to sown seed in row than broadcasting and row spacing of 50-80 cm can be recommended for seed production depending on grass species or cultivars. The selection of optimal production areas depends on soil fertility, the photoperiod and temperature which can interact with rainfall and humidity of the site. The optimum sowing depths was 0-30 mm with some species and cultivars emerging from greater depths than others. With some exceptions, larger seeds were generally able to germinate successfully from greater depths. It was reported that seeds of Brachiaria brizantha and Panicum maximum established better when covered by 20-50 mm. Generally, applying fertilizer nitrogen to seed crops has implications for yield component dynamics such as tiller increasing, number of fertile tillers, floret per spikelet, and seed per head and ultimately increases seed yield and quality. Amounts of nitrogen fertilizer required will depend on species, soil type and rainfall. More often, 100-250 kg of nitrogen per ha and crop and rate more than 300 kg N/ha caused reduction in seed yield by severe plant lodging. For optimum time for nitrogen application, it can be recommended to growers to apply nitrogen in the period from vegetative to spikelet initiation.
Keywords: Planting density; sowing; fertilization; seed yield; quality; tropical areas